Effects of climatic factors on antioxidant quality of tea (Camellia sinensis) in North Bengal - MISRA, TARUN KUMAR; SAHA, ANIRUDDHA; NANDA, ASHIS KUMAR; MANDAL, PALASH (The Indian Journal of Agricultural Sciences, 2022)
Tea [Camellia sinensis (L.) O. Kuntze] is one of the important contributors to the growing economy of North Bengal. The phytochemical and therapeutic qualities of tea prominently altered recently due to continuous change in climatic conditions of North Bengal. The nutraceutical quality of tea is largely dependent on antioxidant attributes. For investigating the relationship between antioxidant attributes and climatic factors, the present field experiment was conducted in 18 tea gardens of Terai, Dooars and Darjeeling Hills of North Bengal during 2012–17. Antioxidant and phytochemical analysis was performed in three different harvest seasons, viz. March, June and December. Phenolic compounds including catechins were low during winter months, and then gradually increased up to warmer spring season. In stress condition, tea plants biosynthesized more flavonoids and high flavour index in Darjeeling hills. However, free-radical scavenging and metal chelating activities were found to increase from spring to winter season. The data were pooled for PCA analysis to determine the relationship between seasonal variations and tea antioxidant quality in each region of North Bengal separately. Different attributes of climatic factors significantly correlated with antioxidant quality and bioactive compounds. Variation in climate is reportedly affecting the antioxidant quality of tea and its shifting pattern grossly influences the key phytochemicals responsible for the flavour of tea.